Gambaran Tingkat Pengetahuan Ibu Hamil Tentang Senam Hamil Untuk Mempersiapkan Fisik Dan Psikologis Dalam Menghadapi Persalinan Di Wilayah Kerja Puskesmas Koto Besar Nagari Koto Ranah Tahun 2023 - Aninda, Dea; Purwati, Rati; Husna, Husna (Bunda Edu-Midwifery Journal (BEMJ), 2023)
Pregnancy exercise is a fitness program intended for pregnant women. By participating in regular and intensive pregnancy exercise, pregnant women can maintain optimal health of their body and fetus. World Health Organization (2018) estimates that worldwide every year more than 585,000 die during pregnancy or childbirth. The death of pregnant women can be prevented by up to 22%, namely through regular antenatal care (ANC) and regular pregnancy exercise. The purpose of this study was to describe the level of knowledge of pregnant women about the benefits of pregnancy exercise to prepare them physically and psychologically for childbirth. The type of research used was quantitative conducted from March 24 to April 4 in 2023. The population in this study were all pregnant women in their second trimester, consisting of 36 people. The sample in this study were all second trimester pregnant women in the working area of ​​the Koto Besar Nagari Koto Ranah Community Health Center as many as 36 people using the total sampling method. The analysis used is univariate. The results of this study indicate that the level of knowledge of pregnant women about the benefits of pregnancy exercise is less than 16 people (44.4), sufficient knowledge of 13 people (36.1), and sufficient knowledge of 7 people (19.4). It is recommended that health workers provide counseling and pregnancy exercise training so that they can increase the knowledge of pregnant women to prepare physically and psychologically for childbirth